The effects of organizational politics on employee motivations to participate in target setting and employee budgetary participation - Lau, James (Chong M.); Scully, Glennda; Lee, Alina (Elsevier, 2018)
© 2018 Elsevier Inc. This research investigates if and how organizational politics affects budgetary participation. It also ascertains if different forms of organizational politics have different effects on budgetary participation. Three forms of organizational politics (going along to get ahead; pay and promotion policies; and general political behavior) are examined. Based on a survey sample of subordinates with managerial responsibilities, the PLS results indicate as follows. As general political behavior is engaged in by the superiors and not the subordinates, its effects on budgetary participation are direct and not attributable to the subordinates’ motivations to participate in target setting. In contrast, as the politics of going along to get ahead is engaged in by the subordinates themselves, its effects on budgetary participation are indirect and via the subordinates’ motivations to participate in target setting. The effects of the politics of pay and promotion policies on budgetary participation are unclear. These results highlight not only the relevance of organizational politics in budgeting, but they also direct attention to where the management of such politics is needed to influence the extent of budgetary participation.